Dependence of the McGurk effect on age and hearing status - Mildner, Vesna; Dobrić, Arnalda (2014)
The McGurk effect is a perceptual phenomenon that is taken as evidence of sensory integration, specifically of auditory and visual information. It occurs when the visual and auditory input are incongruous: e.g. in the presence of the visual stimulus ga and auditory stimulus ba, the typical response is da. Although it is a robust effect, it has been found to depend on factors such as brain lesions, disorders (e.g. SLI, dyslexia, aphasia, ASD), language, gender, etc. Among these factors is age: on the one hand, there is evidence that the strength of the effect in children increases with age ; on the other hand, there are reports of unimodal dominance in school-age children. Studies of the relationship between age at cochlear implant surgery and the effect have shown, for instance, that individuals who were implanted early exhibit a stronger McGurk effect, whereas those who were implanted at a later age rely on visual cues. The aim of our study was to investigate the McGurk effect in children of different ages and hearing status and look for (i) possible relationship between the strength of the effect and age ; and (ii) for the relationship between the effect and hearing level. Our subject pool consisted of 40 children with normal hearing (20 pre-schoolers and 20 elementary school children) and 40 children with varying levels of hearing impairment. We hypothesized that older children would exhibit a stronger McGurk effect compared to the younger group and that in children with hearing impairment the ratio between unimodal dominance and the presence of the McGurk effect would be directly proportional to the severity of hearing loss. A male speaker recorded syllables ba, pa, da, ta, ga, ka. These were edited to produce combinations of audio-visual stimuli which were presented to the subjects in 2 bimodal conditions (congruent audio-visual, incongruent audio-visual), and 2 unimodal conditions (auditory only, visual only). The results mostly support our hypotheses, with some differences among the children who are hearing-impaired, which may be attributed to the rehabilitation method. The results indicate the importance of multisensory approach in hearing impairments therapy.
Projekt MZOS
Projekt MZOS
ENG